Awareness of Safety Among Construction Workers in the Karnali Province Stadium, Birendranagar-Surkhet - Rokaya, Shovansing; Bohara, Asha (Journal of Engineering Issues and Solutions, 2026)
The research study involves in the assessment of the level of safety awareness among construction workers involved in the Karnali Provincial Stadium project. A set of structural questionnaire survey consisting of 84 respondents was conducted to examine their work experience, demographic background, and knowledge of safety procedures. Relative Importance Index (RII) analysis method was used to analysis the ten safety factors, such as the usage of Personal Protective Equipment (PPE), toolbox discussions, supervision and housekeeping. Final findings concludes that one-third of the workforce is illiterate, the whole the construction industry is male dominating, and a significant portion has less than two years of experience. The result from RII shows the strong adherence to basic safety procedures, which reflect the high awareness of proper PPE usage, good housekeeping, and positive worker-supervisor relations. However, medium level awareness was noted in the areas such as, regular safety checks, worker behaviour, and PPE provision. Moreover, very low awareness was noted on the terms such as safety signage and formal safety trainings, which highlight for the improvement areas.The research concludes that the construction workers are highly aware of fundamental safety practices, showing the significant gaps in the knowledge related to insurance, safety communication, and training. Further recommendations includes the implementation of regular safety training, PPE availability, toolbox talks, and enhancing the use of the safety sign and signage.